Clinical and biochemical features associated with BCS1L mutation. Issue 5 (19th September 2012) - Al‐Owain, Mohammed; Colak, Dilek; Albakheet, Albandary; Al‐Younes, Banan; Al‐Humaidi, Zainab; Al‐Sayed, Moeen; Al‐Hindi, Hindi; Al‐Sugair, Abdulaziz; Al‐Muhaideb, Ahmed; Rahbeeni, Zuhair; Al‐Sehli, Abdullah; Al‐Fadhli, Fatima; et al.
Abstract: Our study describes a novel phenotype in a series of nine Saudi patients with lactic acidosis, from four consanguineous families three of which are related. Detailed genetic studies including linkage, homozygosity mapping and targeted sequencing identified a causative mutation in the BCS1L gene. All affected members of the families have an identical mutation in this gene, mutations of which are recognized causes of Björnstad syndrome, GRACILE syndrome and a syndrome of neonatal tubulopathy, encephalopathy, and liver failure (MIM 606104) leading to isolated mitochondrial respiratory chain complex III deficiency. Here we report the appearance of a novel behavioral (five patients) and psychiatric (two patients) phenotype associated with a p.Gly129Arg BCS1L mutation, differing from the phenotype in a previously reported singleton patient with this mutation. The psychiatric symptoms emanated after childhood, initially as hypomania later evolving into intermittent psychosis. Neuroradiological findings included subtle white matter abnormalities, whilst muscle histopathology and respiratory chain studies confirmed respiratory chain dysfunction. The variable neuro‐psychiatric manifestations and cortical visual dysfunction are most unusual and not reported associated with other BCS1L mutations. This report emphasizes the clinical heterogeneity associated with the mutation in BCS1L gene, even within the same family and we recommend that defects in this gene should be considered in the differential diagnosis of lactic acidosis with variable involvement of different organs.